A Novel Bidirectional Isolated DC-DC Converter With High Voltage Gain and Wide Input Voltage - Wu, Yu-En; Ke, Yao-Ting (IEEE transactions on power electronics, 2021)
This article proposes a novel bidirectional isolated dc-dc converter with high voltage gain and wide input voltage, which can be applied to bidirectional power conversion systems. The proposed topology is composed of a bidirectional buck-boost converter and a forward-flyback converter; it has the advantage of higher voltage gain and has continuous current characteristic of the low-side port in step-up and step-down mode. In addition, the proposed topology also has the function of leakage inductance energy recovery, which can improve the efficiency of the converter, reduce the voltage surges on switches, and have the characteristics of zero voltage switching on certain switches. Finally, this paper implements a 500-W bidirectional dc-dc converter to verify the feasibility of the proposed topology. The low-side voltage of the proposed topology is 24, 48, and 55 V; the maximum efficiency in step-up mode are 94.2%, 95.6% and 96.9%, and the maximum efficiency are 92.6%, 94.2% and 94.5% in the step-down mode, respectively.